2016
DOI: 10.1515/jpm-2015-0259
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of visceral and subcutaneous adipose tissue transcriptome in pregnant women with and without spontaneous labor at term: implication of alternative splicing in the metabolic adaptations of adipose tissue to parturition

Abstract: OBJECTIVE The aim of this study was to determine gene expression and splicing changes associated with parturition and regions (visceral vs subcutaneous) of the adipose tissue of pregnant women. STUDY DESIGN The transcriptome of visceral and abdominal subcutaneous adipose tissue from pregnant women at term with (n=15) and without (n=25) spontaneous labor was profiled with Affymetrix GeneChip Human Exon 1.0 ST array. Overall gene expression changes and differential exon usage rate were compared between patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 323 publications
0
3
0
Order By: Relevance
“…It is accepted that SAT and VAT have different compositions and different metabolic influence and thus, each depot has a different transcriptome and proteome [ 44 , 45 , 46 ]. Although obesity is widely known as a risk factor for different pathologies, many studies have shown that being overweight and obesity can exert, in certain cases, a protective role, giving rise to what is known as the “paradox of the obesity”.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that SAT and VAT have different compositions and different metabolic influence and thus, each depot has a different transcriptome and proteome [ 44 , 45 , 46 ]. Although obesity is widely known as a risk factor for different pathologies, many studies have shown that being overweight and obesity can exert, in certain cases, a protective role, giving rise to what is known as the “paradox of the obesity”.…”
Section: Discussionmentioning
confidence: 99%
“…Mazaki-Tovi et al from Israel and the US [11] aimed to determine gene expression and splicing changes associated with parturition and regions (visceral vs. subcutaneous) of the adipose tissue of pregnant women. They reported for the first time evidence of implication of mRNA splicing and processing machinery in the subcutaneous adipose tissue of women in labor compared to those without labor.…”
Section: Rizzo Et Al From Italymentioning
confidence: 99%
“…AS occurs at a fundamental regulatory crossroad between transcription and translation that is conducive to creating protein diversity in mammals [16]. Up to 95% of highly-evolved eukaryotic species, especially human multi-exon genes, have been shown to produce multiple isoforms through AS [17, 18]. More specifically, AS, which takes place in a limited number of genes in the human genome, is thought to play a major role in increasing the functional complexity and diversity of proteins.…”
Section: Introductionmentioning
confidence: 99%